Electrochemical reduction of CO2 on metal electrodes: Fundamentals and applications review - Viva, Federico Andrés (2013)
Carbon dioxide can be converted to compounds such as formic acid, methanol or methane electrochemically. This electrolytic process has been proposed as a way to store energy and produce a number of compounds, most of which are currently obtained from fossil fuels. The electrochemical reduction of CO2 is a challenging subject for the fundamental and applied sciences. An electrocatalyst with high activity and high selectivity is desired, therefore a good understanding of the electro reduction processes, mechanisms and kinetics, is vital. Likewise, from an engineering point of view, the cell or reactor design is also key to maximize the reduced products. In the present review the electrochemical conversion of CO2 to C1 and C2 compounds is evaluated with emphasis in the formation of formic acid. Relevant reports are overviewed with special consideration of the works published in order to take the electroreduction process from lab to a pilot scale.